2018
DOI: 10.1177/1753466618766490
|View full text |Cite
|
Sign up to set email alerts
|

Extended-release oral treprostinil in the management of pulmonary arterial hypertension: clinical evidence and experience

Abstract: Treprostinil diolamine is the first oral prostacyclin approved for the treatment of pulmonary arterial hypertension (PAH) to improve exercise capacity. Clinical studies have demonstrated modest benefit as monotherapy, whereas no difference in exercise capacity was observed with combination therapy. However, these trials were limited by subtherapeutic dosing owing to intolerable adverse effects. Prostacyclin-related adverse effects, such as nausea, diarrhea, headache, flushing, and jaw pain, are prevalent. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Treprostinil, available in intravenous (Remodulin), subcutaneous (Remodulin), oral (orenitram) and inhaled (Tyvaso) formulations, has a more favorable side effect profile than the aforementioned prostanoid agents. Though no formulation is approved for use in children, multiple studies have demonstrated safety with IV, subcutaneous, and inhaled preparations (55)(56)(57). Subcutaneous treprostinil is the most commonly used systemic preparation in children, as it reduces the infectious risk of indwelling intravenous lines and the potential risk of paradoxical air or thrombo-embolism in patients with unrepaired shunt lesions.…”
Section: Prostanoidsmentioning
confidence: 99%
“…Treprostinil, available in intravenous (Remodulin), subcutaneous (Remodulin), oral (orenitram) and inhaled (Tyvaso) formulations, has a more favorable side effect profile than the aforementioned prostanoid agents. Though no formulation is approved for use in children, multiple studies have demonstrated safety with IV, subcutaneous, and inhaled preparations (55)(56)(57). Subcutaneous treprostinil is the most commonly used systemic preparation in children, as it reduces the infectious risk of indwelling intravenous lines and the potential risk of paradoxical air or thrombo-embolism in patients with unrepaired shunt lesions.…”
Section: Prostanoidsmentioning
confidence: 99%
“… 31 Compared with prostanoids, selexipag has greater selectivity for the IP receptor, leading to reduced gastrointestinal intolerance, which has been a dose-limiting side effect with oral treprostinil. 32 , 33 A recent Delphi panel on the use of oral treprostinil suggested aggressive antidiarrheal medication to manage these adverse effects but failed to reach consensus on optimal dosing strategies. 34 In FREEDOM-EV, oral treprostinil was dosed three times a day (TID); 21 although this could help reduce the intensity of adverse effects to allow increasing the dose to a therapeutic level, 34 TID dosing could introduce adherence issues compared with a drug with less frequent dosing.…”
Section: Discussionmentioning
confidence: 99%
“…31 Compared with prostanoids, selexipag has greater selectivity for the IP receptor, leading to reduced gastrointestinal intolerance, which has been a dose-limiting side effect with oral treprostinil. 32,33 A recent Delphi panel on the use of oral treprostinil suggested aggressive antidiarrheal medication to manage these adverse effects but failed to reach consensus on optimal dosing strategies. 34 In FREEDOM-EV, oral Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] Clinical outcomes are most optimal in those patients who can attain higher doses and remain on therapy long term; however, many develop intractable adverse effects (eg, gastrointestinal) or require a switch to other formulations. [33][34][35][36] This study evaluated 15 patients who were newly started on oral treprostinil and those who switched from other treprostinil formulations (intravenous, subcutaneous, or inhaled). Variants in CYP2C8, CYP2C9, and ABCC4 were associated with treatment persistence (defined as maintenance on medication without discontinuation).…”
Section: Treprostinil Metabolism and The Role Of Cyp2c8/cyp2c9mentioning
confidence: 99%